2018
DOI: 10.1111/aji.13069
|View full text |Cite
|
Sign up to set email alerts
|

Day‐7 embryos generate an anti‐inflammatory immune response in peripheral blood immune cells in superovulated cows

Abstract: Problem Recently, we demonstrated both in vitro and in vivo that an immunological crosstalk between Day‐7 embryo and immune cells exists locally in the uterus in cows. The peripheral immune response to early embryos at Day‐7 of pregnancy in cows remains largely unknown. Thus, we aimed to investigate the response of peripheral blood immune cells in the presence of multiple Day‐7 embryos in the uterus in donor cows of embryo transfer program. Method of study Superovulated cows were either inseminated (n = 13) at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…This hypothesis was supported by our previous study, demonstrating that the peripheral blood neutrophils could respond to the IFNT-signal much earlier (D5) than peripheral blood mononuclear cells (D8; Shirasuna et al, 2012 ). Additionally, we reported that superovulated D7 embryos generated an anti-inflammatory immune response in peripheral blood neutrophils through the upregulation of transcripts for anti-inflammatory cytokines (TGFB1 and IL10; Talukder et al, 2019 ). Moreover, it was found that insemination induces rapid and transient infiltrations of neutrophils into the uterine lumen for removal of bacteria, excess/dead sperm, and tissue debris, which enhances uterine clearance and subsequent embryo receptivity ( Katila, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This hypothesis was supported by our previous study, demonstrating that the peripheral blood neutrophils could respond to the IFNT-signal much earlier (D5) than peripheral blood mononuclear cells (D8; Shirasuna et al, 2012 ). Additionally, we reported that superovulated D7 embryos generated an anti-inflammatory immune response in peripheral blood neutrophils through the upregulation of transcripts for anti-inflammatory cytokines (TGFB1 and IL10; Talukder et al, 2019 ). Moreover, it was found that insemination induces rapid and transient infiltrations of neutrophils into the uterine lumen for removal of bacteria, excess/dead sperm, and tissue debris, which enhances uterine clearance and subsequent embryo receptivity ( Katila, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This model could amplify embryo-derived signals in the uterus that can not be easily detected using the single-embryo model. Indeed, we previously found that interferon-stimulated genes were upregulated in circulating immune cells in the superovulation cow model ( Talukder et al, 2019 ). Furthermore, we used the Japanese Black cows that were prepared exclusively for embryo donors and have only one-time experience of pregnancy and lactation, so their responsiveness to hormone treatment was expected to be highly homogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…In ruminants, IFN-τ is an important maternal gestation-recognition signaling factor secreted by embryonic trophoblast cells [ 51 ], that is highly expressed during embryo implantation and stimulates significant upregulation of ISG15 [ 52 ]. The establishment of pregnancy requires transient regulation of innate and adaptive maternal immunity [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found significant antiviral activity in the uterine vein's blood 15 and 16 days after conception (Bott et al, 2010;Romero et al, 2015). IFNT enters the uterine vein and, as a result, stimulates the expression of multiple ISGs and immune response genes in blood cells to help maintain pregnancy (Green et al, 2010;Shirasuna et al, 2012;Talukder et al, 2019). Collectively, in addition to the modulatory effects on embryo development, endometrial and luteal environments, IFNT also coordinates the maternal immune response during the MRP (Hansen et al, 2017).…”
Section: Interferon Tau (Ifnt)mentioning
confidence: 99%
“…PMNs produce numerous anti-and pro-inflammatory cytokines (Mantovani et al, 2011) that are essential in pregnancy. In pregnant cows, PMNs showed an anti-inflammatory response with greater expression of TGFB, IL10, and forkhead box P3 (FOXP3) (Talukder et al, 2019). Pro-inflammatory cytokines data have shown biases in different studies; however, expression patterns seem to increase according to the development of pregnancy (Figure 1) (Fiorenza et al, 2021;Manjari et al, 2016;Sheikh et al, 2019;Shirasuna et al, 2012).…”
Section: Maternal Recognition Of Pregnancy and Neutrophilsmentioning
confidence: 99%